Glycerine Production and Transformation An Innovative Platform for Sustainable Biorefinery and Energy - Frediani, Marco; Bartoli, Mattia; Rosi, Luca (IntechOpen, 2019)
The increase in the amount of glycerin in the market is a burden for all producers, especially those operating in the biodiesel sector: reuse options are in fact limited for the management of this by-product. Glycerol enhancement has therefore become a priority to improve the sustainability of the biodiesel industry. Nevertheless, the multifunctionality of glycerol makes it a promising precursor for different types of production (fuel/biofuel, chemical products). This conversion has therefore become a subject of multifaceted research that requires an exchange of knowledge across many sectors. In this book, different disciplines (chemistry, biology, engineering, etc.) have been taken into consideration to propose an interdisciplinary point of view on different aspects.